Body composition changes in elite male weightlifters during a ten months training for international competition - Georgiou, E.; Virvidakis, K.; Douskas, G.; Deftereos, S.; Proukakis, C. H. (1999)
The aim of this study was to examine the body composition in male elite weightlifters (WL) and to monitor the changes in body composition during the training period preceding an international competition. Data were collected from 10 elite WL, all been members of the national Greek team, and 10 age- and weight matched male controls. Whole body composition analysis was carried out by Dual-Energy X-Ray Absorptiometry (DEXA) by means of a Hologic 4500W densitometer (Hologic Co., Waltham, MA, USA) using their whole body analysis software. DEXA is a non-invasive method allowing the rapid and precise quantitative estimation of body composition. The WL's performance was homogenised from the different weight categories by using the Sinclair Index. Measurements were performed off season (10 months before) and repeated 10 days before the contest. WL had higher bone mineral density (BMD), lean mass (L) and lower fat mass (F) than the controls (WL: BMD= 1.38 g/cm2, L=64.6Kg, F=12.1 Kg; Controls: BMD=1.12g/cm2, L=57.1Kg, F=22.5Kg). During the training period, WL lost 2.34 Kg of F, while they exhibited a trend towards L gain (0.74Kg). Higher performance (Sinclair Index) was associated with lower off-season %F (r=-0.56, p= 0.03), higher off-season %L (r=0.56, p=0.03) and lower F reduction during training for competition (r=0.91, p=0.0001). These results indicate that good physical condition, monitored by the off-season metabolically more optimal body composition profile as assessed by DEXA, is associated with higher scores in competition.